Association of triglyceride-glucose-body mass index with all-cause mortality among individuals with cardiovascular disease: results from NHANES - Yiaoran Sun; Yiaoran Sun; Yuecheng Hu; Yuecheng Hu (Frontiers in Endocrinology, 2025)
BackgroundThe objective of this study was to explore the relationship between the triglyceride-glucose-body mass index (TyG-BMI) and all-cause mortality rate and to determine valuable predictive factors for the survival status of patients with cardiovascular disease (CVD).MethodsConduct a study on CVD patients in the NHANES database from 2007 to 2016. Patients were divided into four groups based on the weighted quartiles of TyG-BMI. Kaplan-Meier curves, Cox regression, and restricted cubic spline (RCS) were used to analyze the correlation between this index and all-cause mortality. Receiver operating characteristic (ROC) curves were used to evaluate its predictive ability, sensitivity, and specificity.ResultsThis study included 1085 patients, and revealed significant differences in survival rates among patients with different TyG-BMI levels. Patients in the higher TyG-BMI group have a lower mortality risk, yet there is no evident non-linear relationship. The ROC curve indicates that this indicator can serve as a predictive value for mortality in CVD patients, demonstrating good sensitivity and specificity.ConclusionThis study found a significant association between TyG-BMI index and all-cause mortality in patients with CVD. TyG-BMI can be used as a predictive indicator of all-cause mortality in CVD patients.